2021
DOI: 10.1016/j.rmed.2021.106440
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection in severe Alpha 1-antitrypsin deficiency: Looking for a rationale

Abstract: The clinical manifestations of COVID-19 are heterogeneous: 46.4% of patients admitted into hospital reported to have at least one comorbidity. Comorbidities such as COPD, diabetes, hypertension and malignancy predispose patients with Covid-19 to adverse clinical outcomes. Alpha 1-antitrypsin deficiency (AATD) is a genetic disorder caused by pathological mutation(s) in the SERPINA1 gene resulting in an imbalance in proteinase activity which may lead to premature emphysema and COPD.Our aim was to investigate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…The authors found a higher frequency of SARS-CoV-2 infection in the AATD cohort (3.8%) compared to the national data regarding infection, and patients with severe AATD had a relative risk of 8.8 (95% confidence interval (CI): 5.1–20.0; p < 0.0001) for symptomatic SARS-CoV-2 infection. Moreover, the relative risk (RR) was higher in patients with AATD and pre-existing lung diseases (RR 13.9; 95% CI: 8.0–33.6; p < 0.001) [ 30 ].…”
Section: Aatd and Covid-19: Geographical Overlap And Data From Clinical Registriesmentioning
confidence: 99%
“…The authors found a higher frequency of SARS-CoV-2 infection in the AATD cohort (3.8%) compared to the national data regarding infection, and patients with severe AATD had a relative risk of 8.8 (95% confidence interval (CI): 5.1–20.0; p < 0.0001) for symptomatic SARS-CoV-2 infection. Moreover, the relative risk (RR) was higher in patients with AATD and pre-existing lung diseases (RR 13.9; 95% CI: 8.0–33.6; p < 0.001) [ 30 ].…”
Section: Aatd and Covid-19: Geographical Overlap And Data From Clinical Registriesmentioning
confidence: 99%
“…COVID-19 cases are increased in areas of Italy with an increased prevalence of AAT deficiency 11 . AAT deficient subjects were 8.8-fold more likely to have symptomatic COVID-19 than the general Italian population 12 . Shapira and colleagues 13 found a significant direct correlation between the frequency of the protease inhibitor (Pi)Z and PiS alleles with COVID-19 death rates in 67 countries.…”
Section: Introductionmentioning
confidence: 87%
“…Indeed, several studies pointed to a tentative link between lower blood AAT levels and severe Covid-19, suggesting that AAT deficiency contributes to Covid-19 fatalities (Faria et al, 2021;Ferrarotti et al, 2021;Shapira et al, 2020;Shimi et al, 2021;Vianello & Braccioni, 2020). Indeed, bioengineered AAT, which is approved for treating lung inflammation in AAT deficient individuals, was proposed as potential therapeutic for Covid-19 (Marzouk et al, 2021;Yang et al, 2020;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced expression of SERPINA1 , coding for alpha‐1 antitrypsin (AAT), observed following chronic d ‐galactose treatment, also suggests higher SARS‐CoV‐2 infection load: AAT readily inhibits TMPRSS2 (Azouz et al, 2021; Wettstein et al, 2021), which is essential for priming SARS‐CoV‐2 for cell entry (Azouz et al, 2021; Hoffmann et al, 2020). Indeed, several studies pointed to a tentative link between lower blood AAT levels and severe Covid‐19, suggesting that AAT deficiency contributes to Covid‐19 fatalities (Faria et al, 2021; Ferrarotti et al, 2021; Shapira et al, 2020; Shimi et al, 2021; Vianello & Braccioni, 2020). Indeed, bioengineered AAT, which is approved for treating lung inflammation in AAT deficient individuals, was proposed as potential therapeutic for Covid‐19 (Marzouk et al, 2021; Yang et al, 2020; Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%